2007
DOI: 10.5194/bg-4-803-2007
|View full text |Cite
|
Sign up to set email alerts
|

Variability of annual CO<sub>2</sub> exchange from Dutch grasslands

Abstract: Abstract. An intercomparison is made of the Net Ecosystem Exchange of CO 2 , NEE, for eight Dutch grassland sites: four natural grasslands, two production grasslands and two meteorological stations within a rotational grassland region. At all sites the NEE was determined during at least 10 months per site, using the eddy-covariance (EC) technique, but in different years. The NEE does not include any import or export other than CO 2 . The photosynthesis-light response analysis technique is used along with the r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 28 publications
7
41
0
Order By: Relevance
“…fertilisation) of organic soils stimulate the aerobic oxidation of previously accumulated organic matter, promoting CO 2 and nitrous oxide (N 2 O) emissions while reducing methanogenesis (Byrne et al, 2004;Freibauer et al, 2004;Nieveen et al, 2005;Jacobs et al, 2007;Drösler et al, 2013;Schrier-Uijl et al, 2013). However, inter-regional spatio-temporal variability of CO 2 flux is high, particularly in western Europe.…”
Section: F Renou-wilson Et Al: the Impacts Of Drainage Nutrient Stmentioning
confidence: 99%
“…fertilisation) of organic soils stimulate the aerobic oxidation of previously accumulated organic matter, promoting CO 2 and nitrous oxide (N 2 O) emissions while reducing methanogenesis (Byrne et al, 2004;Freibauer et al, 2004;Nieveen et al, 2005;Jacobs et al, 2007;Drösler et al, 2013;Schrier-Uijl et al, 2013). However, inter-regional spatio-temporal variability of CO 2 flux is high, particularly in western Europe.…”
Section: F Renou-wilson Et Al: the Impacts Of Drainage Nutrient Stmentioning
confidence: 99%
“…However, the exact budget will depend on the vegetation and its canopy photosynthetic capacity and can be difficult to predict if a wetland is not yet in equilibrium, for example following restoration . It is known that site management plays a role, too, and Jacobs et al (2007) reported a rather unexpected average annual CO 2 release of 220±90 g C m −2 for four Dutch grasslands on organic soils having a relatively high water table and including both managed and unmanaged sites. In contrast, Hendriks et al (2007) observed a consistent net CO 2 uptake between 232 and 446 g C m −2 a −1 for a restored wet grassland with neither grazing nor cutting.…”
Section: Impacts Of Climate and Management On Co 2 Fluxesmentioning
confidence: 99%
“…with R 10 the base respiration rate at 10 ∘ C, E a the ecosystem sensitivity coefficient in K, R * the universal gas constant, and T s (t) the instantaneous upper soil layer temperature in K. This Lloyd and Taylor (1994) (Jacobs et al, 2007). Also, since we do not have soil temperature in the reanalysis weather data, we replace T s in equation (10) with the 2 m air temperature (T air ), assuming that the error introduced by the larger diurnal amplitude of T air will average out over 24 h. We hence compute the daily soil respiration (R soil , in g C m −2 d −1 ) by integrating R s over a day and converting it from mg CO 2 to g C with a conversion factor (C f ):…”
Section: Soil Respiration and Net Ecosystem Exchangementioning
confidence: 99%
“…Note that in practice, the R 10 and E a parameters from equation (10) were estimated from nighttime eddy-covariance NEE measurements, when no GPP and no R growth occur (see Jacobs et al, 2007). As a result, R soil represent not only R het as originally intended but also the whole plant maintenance respiration, both variables dependent on T air .…”
Section: Soil Respiration and Net Ecosystem Exchangementioning
confidence: 99%